Ex Vivo Fluorescein-Assisted Confocal Laser Endomicroscopy (CONVIVO® System) in Patients With Glioblastoma: Results From a Prospective Study - Acerbi, Francesco; Pollo, Bianca; De Laurentis, Camilla; Restelli, Francesco; Falco, Jacopo; Vetrano, Ignazio G.; Broggi, Morgan; Schiariti, Marco; Tramacere, Irene; Ferroli, Paolo; DiMeco, Francesco (Frontiers in Oncology, 2020)
Background: Confocal laser endomicroscopy (CLE) allowing intraoperative near real-time high-resolution cellular visualization is a promising method in neurosurgery. We prospectively tested the accuracy of a new-designed miniatured CLE (CONVIVO system) in giving an intraoperative first-diagnosis during glioblastoma removal. Methods: Between January and May 2018, 15 patients with newly diagnosed glioblastoma underwent fluorescein-guided surgery. Two biopsies from both tumor central core and margins were harvested, dividing each sample into two specimens. Biopsies were firstly intraoperatively ex -vivo analyzed by CLE, subsequently processed for frozen and permanent fixation, respectively. Then, a blind comparison was conducted between CLE and standard histological permanent section analyses, checking for CLE ability to provide diagnosis and categorize morphological patterns intraoperatively. Results: Blindly comparing CONVIVO and frozen sections images we obtained a high grade rate of concordance in both providing a correct diagnosis and categorizing patterns at tumor central core (80% and 93,3%, respectively) and at tumor margins (80% for both objectives). Comparing CONVIVO and histological permanent sections, concordance resulted similar at central core (total/partial concordance in 80% and 86,7% for diagnosis and morphological categorization, respectively) and lower at tumor margins (66,6% for both categories). Time from fluorescein injection and time from biopsy sampling to CONVIVO scanning was 134  31 minutes (122-214min) and 9.23 minutes (1-17min), respectively. Mean time needed for CONVIVO images interpretation was 5.74 minutes (1-7min). Conclusions: The high grade rate of diagnostic/morphological consistency found between CONVIVO and frozen section analyses suggests the possibility to use CLE as a complementary tool for intraoperative diagnosis of ex -vivo tissue specimens during glioblastoma surgery.